POLA ASUH ORANG TUA DALAM PERKEMBANGAN MORAL REMAJA (STUDI KASUS DI DESA PERNEK - Dian Supandi; Lukmanul Hakim; Roni Hartono (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
This study aims to describe parenting style in adolscent moral development (case study in the village of pernek). In this study the researchers made 3 parents from different families as research subjects and 3 (three) children from each research subject. The selection of the three subjects is based on different parenting methods used in the family. This study uses a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentary. The results of this study indicate that parenting with authoritarian and permissive methods are more dominantly applied by subjects 1 and 2 where this upbringing can form a bad moral for children (adolescents). Then parenting with democratic methods is more dominant in subject 3 where this upbringing can form a good moral for children (adolescents). Authoritarian parenting has a low